2001
DOI: 10.1200/jco.2001.19.3.843
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Safety and Pharmacokinetic Study of Recombinant Human Anti-Vascular Endothelial Growth Factor in Patients With Advanced Cancer

Abstract: rhuMAb VEGF was safely administered without dose-limiting toxicity at doses ranging up to 10 mg/kg. Multiple doses of rhuMAb VEGF were well tolerated, and pharmacokinetic studies indicate that doses of > or = 0.3 mg/kg have a half-life similar to that of other humanized antibodies. Subsequent trials will explore rhuMAb VEGF alone and in combination chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
461
3
18

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 875 publications
(497 citation statements)
references
References 12 publications
15
461
3
18
Order By: Relevance
“…Note however that this did not take account of the context of that practice as either research or clinical. So bevacizumab is dated as 2001 because of its first use in advanced solid tumours at that time (Gordon et al 2001).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Note however that this did not take account of the context of that practice as either research or clinical. So bevacizumab is dated as 2001 because of its first use in advanced solid tumours at that time (Gordon et al 2001).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…26 the role of veGF in thyroid signaling is uncertain. 40,41 unlike treatment with antiangiogenic tKis, bevacizumab is not associated with altered thyroid homeostasis. 42,43 other factors, such as platelet derived growth factor α and c Kit, have roles in thyroid homeostasis, but so far no data have been published.…”
Section: Reviewsmentioning
confidence: 99%
“…[19][20][21][22][23] Phase 1 studies in various solid tumors demonstrated a half-life of nearly 3 weeks, and no dose-limiting toxicities. 24,25 With this safety information, and in light of remarkable successes in other cancers including those of the breast and colon, oncologists began to use bevacizumab for the treatment of patients with recurrent glioblastoma. In the first such report, 21 patients were presented who received bevacizumab and irinotecan as salvage therapy for recurrent glioblastoma.…”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%